PENINGKATAN KEMAMPUAN LITERASI DIGITAL GURU NON-FORMAL DENGAN PEMANFAATAN MEDIA HAND PUPPET DALAM DONGENG - Abd. Qadir Muslim; Langgeng Setyono; Kadarisman Hidayat; Ridho Rifki Fadillah (Journal Publicuho, 2022)
The development of information technology and the internet affect the abundance of digital information flows. This reflection also indicates that students in Indonesia, who are the digital native generation, have a strong dependence on the internet. In addition, the weak information literacy that plagues educators affects unattractive learning and the quality of students is not adaptable. Therefore, teachers as educators and school library staff as educational staff are required to be competent incapable of information literacy so that they can teach digital literacy continuously. The method in this study uses a Participatory Action Research (PAR) approach, which is located at Al-Jannah Jambon KB/TK, Pakis District, Malang Regency. The purpose of this literacy improvement training is to improve teachers' understanding and abilities related to digital literacy competencies, provide insight into alternative learning methods that can be used using technology, improve teacher skills in making interactive learning media to build classroom activity. The PAR results show that with the digital literacy workshop on hand puppets, these non-formal teachers feel helped in their efforts to improve digital literacy. On the other hand, teachers also find it easier to be creative.